Monitoramento costeiro das praias de São Bento do Norte e Caiçara do Norte RN: implicações para o pólo petrolífero de Guamaré - Tabosa, Werner Farkatt (2002)
This dissertation the results of a research developed in the area of São Bento do Norte and Caiçara do Norte, northern coast of the State of Rio Grande do Norte, during the period of June of 2000 to August of 2001, in the ambit of the projects MAMBMARÉ (CNPq/CTPETRO) and PROBRAL (CAPES/DAAD).The objective principal of this research was the characterization of the sedimentary dynamics of this coast, with base in data of coastal process (winds, currents, waves and tides), with topographical risings (beach profiles and dunes), satellite images and sedimentary analyses. The more specific objectives were accomplished the coastal monitoring of this coast, to verify the maintenance of an erosive tendency or progradacional after the groynes construction for contention of the erosion in the beach of Caiçara do Norte, as well as to verify the influence of the features of bottom of the platform interns adjacent on the pole petroliferous of Guamaré. The executed monitoramento allowed to identify that the movement of the sediments, along the year, in that area, is cyclical, reaching the largest oscillations during the months of winter (deposition) and they will summer (erosion). The sedimentologic studies indicated a general tendency for sands quartzosas, with gravel presence, moderately to good selected, with asymmetry predominantly negative. In agreement with the parameter of Dean (1957), used in the identification of the state morfodinâmico of the beaches, monitored beaches, are basically reflectivas with tendency to middlemen, what frames that space of the coast norteriograndense, as a space strongly vulnerable to erosive processes. The studies developed in the platform, it interns of this area, allowed to visualize for the first time, in large scale, the distribution of the features of the submarine bottom to the batométrico coat of 25 meters. Being pointed out the presence of a high one topographical submerged, with about 5 meters of height, 1 km of width and more than 24 meters of extension, located in the platform it interns in front of São Bento do Norte; coincident with the trend of the system of flaws of Carnaubais. This feature relay an important paper on the control of the sedimentary processes and oceanographic, as well as in the coastal evolution of this area of the RN state, and they affect the area of the pole petroliferous of Guamaré directly. These results contribute to a better knowledge of the processes in the area, and consequently as subsidies implantation of measures of coastal and environmental protection for the cities of São Bento do Norte and Caiçara do Norte, as well as to understand how the geological-sedimentary processes and oceanographic, in this area, are influencing the characteristics geoambientais of the pole petroliferous of Guamaré